In Vitro and in Vivo Antibacterial Activities of Cyanidinum Chloride-loaded Liposomes against a Resistant Strain of Pseudomonas aeruginosa - Gharib, Amir; Faezizadeh, Zohreh; Mesbah-Namin, Seyed Ali Reza (Planta Medica, 2013)
Pseudomonas aeruginosa remains a common cause of wound infections. Different studies have shown that the entrapment of plant-derived materials in liposomes could increase their antibacterial activity against Pseudomonas aeruginosa. The aim of this study was to prepare cyanidinum chloride-loaded liposomes and evaluate their in vitro and in vivo efficacy against a resistant strain of Pseudomonas aeruginosa ATCC 15692. Cyanidinum chloride-loaded liposomes were prepared by extrusion method. The minimum inhibitory concentrations of cyanidinum chloride in the free and liposomal forms against Pseudomonas aeruginosa ATCC 15 692 were determined in vitro by broth dilution method. The in vitro killing rates for free and liposomal cyanidinum chloride were analyzed. Ultimately, the in vivo therapeutic efficacy of the prepared liposomes in mice skin infected by ATCC 15692 was investigated. The minimum inhibitory concentrations of the free and liposomal forms of cyanidinum chloride against ATCC 15692 were 1.5 × 10−3 and 7.7 × 10−4 M, respectively. In vivo treatment with the free and cyanidinum chloride-loaded liposomes resulted in almost 40 and 100 % survival rates, respectively. Our results showed that cyanidinum chloride-loaded liposomes would be a good choice for the treatment of wound infection caused by Pseudomonas aeruginosa because of their high effectiveness.
Keywords: cyanidinum chloride; liposome; Pseudomonas aeruginosa; killing rates; in vitro; in vivo